Knowledge and Attitude of Hypertension Patients towards Traditional Medicines: A Cross-sectional Study at Public Health Center, Siak, Riau - Husnawati, Husnawati; Dewi, Ratna Sari; Ningsih, Yozi Fiedya; Fitriani, Dewi (Fakultas Farmasi Universitas Andalas, 2023)
Hypertension is a significant global concern associated with severe cardiovascular ailments, including stroke, myocardial infarction, cardiac insufficiency, and renal dysfunction. Traditional medicines (TM) represent a potential alternative treatment modality for the management of hypertension. Hence, this study aims to establish the relationship between individuals' knowledge and attitudes about using TM among hypertension patients. This observational research utilizes a descriptive-analytic approach with a cross-sectional design. Validated questionnaires were used to collect the knowledge and attitudes data of respondents. The correlation between knowledge and attitudes was analyzed with the Spearman test using SPSS version 24. A total of 102 respondents were successfully acquired using purposive non-probability sampling. The results of this study indicate a significant statistical relationship between the knowledge and attitudes of hypertensive patients regarding the utilization of TM (p-value 0.000). Furthermore, a moderate positive correlation (rs 0.493) was observed, suggesting that an improvement in knowledge is associated with a corresponding enhancement in the attitude of hypertensive patients towards TM.